Climatic conditions influence emerging mycotoxin presence in wheat grown in Romania – A 2-year survey. (October 2017) - Stanciu, Oana; Juan, Cristina; Miere, Doina; Dumitrescu, Alexandru; Bodoki, Ede; Loghin, Felicia; Mañes, Jordi
Abstract: The correlation between the occurrence of four enniatins (ENA, ENA1, ENB, and ENB1) and beauvericin (BEA) and the weather parameters during anthesis and preharvest period was studied in 97 wheat samples collected in 2014 and 2015 across three counties from central and south Romania (Braşov, Dâmboviţa, and Teleorman). The highest mean values of ENA (16.1 μg kg −1 ) and ENB (147.1 μg kg −1 ) were measured in the samples from Braşov county in the harvest year 2015, whereas for ENA1 and ENB1 the highest means (55.2 μg kg −1, and 108.0 μg kg −1, respectively) were noted in samples from Teleorman county in 2014. Statistically significant differences ( P  < 0.05) were identified between ENA1 and ENB1 and the harvest year, coupled with a strong correlation with the weather parameters (ENA1: r s  = 0.8745 and r s  = 0.9326; ENB1: r s  = 0.7814 and r s  = 0.8909, for temperature and precipitation, respectively). Principal component analysis revealed that the influence of weather parameters on emerging mycotoxin concentrations in wheat samples varied by region. This study showed that the presence and levels of emerging mycotoxins are related to weather parameters from the respective Romanian region. Highlights: 97 Romanian whole wheat samples were investigated for emerging mycotoxins. Regional differences were observed, correlated with the climatic conditions. Anthesis (May) and pre-harvest period (July) are critical for ENs and BEA. Monthly precipitation at least 20 mm greater than long-term averages increase ENs.